2018
DOI: 10.1589/jpts.30.1408
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a virtual reality video game exercise program on upper extremity function and daily living activities in stroke patients

Abstract: [Purpose] This study examined the effects of training using virtual reality games on stroke patients’ functional recovery. [Paticipants and Methods] Twenty-four hemiplegia patients whose disease duration was longer than six months participated in this study. The participants were divided at random into a control group (n=12), which received traditional rehabilitation therapy, and an experimental group (n=12), which received both traditional rehabilitation therapy and training using virtual reality games. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…Previous results suggest a significant difference between groups on the FMUE scale, while muscle strength reports have not shown significant differences pre-and post-therapy. In our study, the increase in muscle strength of the upper extremity may be explained by the addition of wrist weights during VR training and the study design [9,35].…”
Section: Discussionmentioning
confidence: 78%
“…Previous results suggest a significant difference between groups on the FMUE scale, while muscle strength reports have not shown significant differences pre-and post-therapy. In our study, the increase in muscle strength of the upper extremity may be explained by the addition of wrist weights during VR training and the study design [9,35].…”
Section: Discussionmentioning
confidence: 78%
“…51 Moreover, a systematic review found that immersive VR (VRi) presents additional clinical benefits when compared with conventional vestibular training (performance and repetition of exercises in a motivational environment, oriented tasks, multisensory stimulation, extrinsic feedback and promotion of adherence). [52][53][54][55][56][57] The VR induces neuroplastic changes in neurological affection as MS. 58 Within VRi, the modality that integrates physical activity in a virtual environment with mentioned advantages is exergame, that has proven to be effective for neurological diseases. 59 60 Moreover, despite exercising through a VR system, it is perceived as less exhausting, 61 while the subject is exposed to a large variety of environments boosting the vestibular mechanism of habituation.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Several research studies have used the FMA-UE to assess the effects of the intervention on motor function in the upper limb. Their results suggest a significant difference between intervention groups, while the improvement of muscle strength has not shown significant differences before and after the intervention [ 17 , 52 , 53 ]. In our study, the increase in muscle strength in the upper limb and the differences found between the experimental and control groups can be explained by the placement of weights on the wrists during SVR training, coinciding with findings by Miclaus et al [ 54 ].…”
Section: Discussionmentioning
confidence: 99%